Ultra-compact integrated terahertz modulator based on a graphene metasurface - Kim, Myunghwan; Kim, Sangin; Kim, Soeun (Optics Letters, 2021)
We propose a new type of a mid-infrared ultra-compact optical modulator composed of a graphene metasurface. Unlike the previously proposed schemes based on loss variation of materials or interference, the proposed one utilizes the unique topological characteristic of the isofrequency contour in the hyperbolic metasurface to modulate the transmission. The designed modulator provides a modulation depth of 10.7 dB, the length of which is 750 nm, corresponding to ∼1/30 of an operating wavelength.
Keywords: Integrated terahertz; Loss variation; Metasurface; Midinfrared; Modulation depth; Operating wavelength; Topological characteristics